2017
DOI: 10.1007/jhep07(2017)136
|View full text |Cite
|
Sign up to set email alerts
|

D-dimensional charged Anti-de-Sitter black holes in f (T) gravity

Abstract: We present a D-dimensional charged Anti-de-Sitter black hole solutions in f (T ) gravity, where f (T ) = T + βT 2 and D ≥ 4. These solutions are characterized by flat or cylindrical horizons. The interesting feature of these solutions is the existence of inseparable electric monopole and quadrupole terms in the potential which share related momenta, in contrast with most of the known charged black hole solutions in General Relativity and its extensions. Furthermore, these solutions have curvature singularities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 63 publications
11
76
0
Order By: Relevance
“…We notice that setting the rotational parameter Ω = 0, we find the static charged black hole configuration, as in Ref. [26]. Moreover, turning off the mass parameter M and Q, the metric (13) reduces to, the 4D AdS metric in an uncommon coordinate system.…”
Section: B Rotating Charged Ads Black Holessupporting
confidence: 64%
“…We notice that setting the rotational parameter Ω = 0, we find the static charged black hole configuration, as in Ref. [26]. Moreover, turning off the mass parameter M and Q, the metric (13) reduces to, the 4D AdS metric in an uncommon coordinate system.…”
Section: B Rotating Charged Ads Black Holessupporting
confidence: 64%
“…related to this, a numerous of research papers have been focused on the study of black hole solutions, as e.g. [5][6][7][8][9][10][11][12][13][14], and neutron stars solutions [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. We should note that f (R) theories can be related with theories of Brans-Dicke type (see, e.g., [29]), in particular with the ones involving a scalar and a potential of gravitational origin [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…(iv) The ( ) gravitational theory whose field equations are of second order [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] (v) The one known as ( ) theories which we focused the present study on [81] It is shown that ( ) gravitational theories are able to describe the whole story of cosmology starting from inflation to the present accelerated expansion epoch [82]. Many applications of ( ) gravitational theories have been carried out [83,84].…”
Section: Introductionmentioning
confidence: 99%